Synthesis, characterization and antibacterial activity of a graphene oxide based NiO and starch composite material. Issue 4 (24th November 2020) - Dewangan, Ranjana; Asthana, Anupama; Singh, Ajaya Kumar; Carabineiro, Sónia A. C.
Abstract: This work reports a novel, facile and hydrothermal approach to prepare graphene oxide/NiO/Starch composite materials (GO/NiO/Starch). The composite materials were fully characterized by Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray analysis (EDS), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Raman spectroscopy and X-ray photo-electron spectroscopy (XPS), and Thermo gravimetric analysis (TGA-DTA). Furthermore, the antibacterial properties of NiO and starch decorated graphene oxide were tested against Staphylococcus aureus by using the well diffusion method. The obtained results show that the GO/NiO/Starch composite material has a substantial antibacterial activity against Staphylococcus aureus . GRAPHICAL ABSTRACT: UF0001 This is the flowchart of synthesis, characterization and biological activity of graphene oxide based NiO and starch composite materials: